Kesiapan Perpustakaan dalam Implementasi Teknologi Informasi (Studi Kasus Perpustakaan UIN Sumatera Utara Medan) - Habiburrahman, Habiburrahman (Universitas Negeri Padang, 2020)
This research aims to determine the level of ereadiness at Library of UIN Sumatra Utara Medan. This research uses mix method concurrent triangulation model. The instrument of e readiness used in this research was developed by Mutula & Brakel. Data collection techniques used in this research are questionnaire to get the quantitative data and deep interview and observation to get the qualitative data. Population which become subject in this research is 16 people who are library staff at Library of UIN Sumatera Utara Medan. The sample in this research is determined by saturation sampling technique to get quantitative data and purposive sampling teechnique to get qualitative data. Quantitative analysis showed that in the enterprise readiness segment, the score was 2.93 which means ready, in human resource readiness segment obtained the score of 2.63 which is categorized as ready but has very low e-readiness score because the library doesn’t have sufficient profesional staff, in the information readiness segment the score was 2.89 which is categorized ready, in ICT readiness segment obtained 2.94 which is categorized ready, while in the of external environment readiness segment obtained the score of 2.88 which is also in the ready category. While the qualitative analysis got the result that the ICT infrastructure is quite ready for the implementation of information technology altough there are still component that have not been feasible which is the quality of the internet WiFi network for users. In addintion, in terms of professional human resources, the library doesn’t have edaquate experts. For that it is necessary to add some profesionals in the field of information technology also the provision of continuous training to the staff and librarians by involving them in professional trainings so that the librarians and library staff have sufficient ability to handle the problems that occur in the implementation of information technology.